A computational and experimental approach to validating annotations and gene predictions in the Drosophila melanogaster genome - Yandell, Mark (National Academy of Sciences, 2005)
Five years after the completion of the sequence of the Drosophila melanogaster genome, the number of protein-coding genes it contains remains a matter of debate; the number of computational gene predictions greatly exceeds the number of validated gene annotations. We have assembled a collection of >10,000 gene predictions that do not overlap existing gene annotations and have developed a process for their validation that allows us to efficiently prioritize and experimentally validate predictions from various sources by sequencing RT-PCR products to confirm gene structures. Our data provide experimental evidence for 122 protein-coding genes. Our analyses suggest that the entire collection of predictions contains only ≈700 additional protein-coding genes. Although we cannot rule out the discovery of genes with unusual features that make them refractory to existing methods, our results suggest that the D. melanogaster genome contains ≈14,000 protein-coding genes.